2017
DOI: 10.1182/blood-2017-06-788216
|View full text |Cite
|
Sign up to set email alerts
|

In vivo–generated thrombin and plasmin do not activate the complement system in baboons

Abstract: Sepsis concurrently activates both coagulation and complement systems. Although complement activation by bacteria is well documented, work in mice and in vitro suggests that coagulation proteases can directly cleave complement proteins. We aimed to determine whether generation of coagulation proteases in vivo can activate the complement cascade in 2 highly coagulopathic models. We compared temporal changes in activation biomarkers of coagulation (thrombin-antithrombin [TAT]), fibrinolysis (plasmin-antiplasmin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…1 T heir observation appears in sharp contrast with earlier studies that did identify a potential for thrombin and plasmin to activate the complement system. 2,3 The apparent contradiction thus raises a fundamental question: Is this a case of "in vivo veritas," or are there experimental or physiological grounds that may explain the differences?…”
Section: Universität Zu Lübeckcontrasting
confidence: 54%
See 1 more Smart Citation
“…1 T heir observation appears in sharp contrast with earlier studies that did identify a potential for thrombin and plasmin to activate the complement system. 2,3 The apparent contradiction thus raises a fundamental question: Is this a case of "in vivo veritas," or are there experimental or physiological grounds that may explain the differences?…”
Section: Universität Zu Lübeckcontrasting
confidence: 54%
“…1 What unites these diverse infusion of a lethal dose of E coli induced protracted activation of coagulation and fibrinolytic pathways when compared with the "pure coagulopathy" model, as evidenced by delayed but strong consumption of prothrombin, plasminogen, and fibrinogen. In addition, the sepsis model also fueled strong complement activation.…”
Section: Universität Zu Lübeckmentioning
confidence: 99%
“…Second, lepirudin specifically blocks thrombin, both limiting the available assays of coagulation and masking the contributions of thrombin itself. Thrombin has been postulated to activate complement directly , although a very recent study performed in septic baboons did not detect any complement activation by thrombin (or plasmin) . Likewise, the recent focus on the cross‐talk between the many plasma cascade systems in thromboinflammation has revealed that thrombin can affect both platelet and endothelial cell function .…”
Section: Discussionmentioning
confidence: 99%
“…Various enzymes involved in coagulation and fibrinolysis have been proposed as C5 convertases, with the strongest evidence supporting plasmin , but these models all involve tissue damage as well as protease activation. Baboons with sepsis triggered by either Escherichia coli or lipopolysaccharide (LPS) showed no evidence of complement activation by either thrombin or plasmin, but the role of platelets in these models was not investigated . To determine whether any of the coagulation enzymes can activate complement in vivo , cleavage of C5 to C5a and C5b should be studied in the absence of C3 in the C3‐deficient mouse in an appropriate complement activation‐mediated disease model.…”
Section: Cross‐activation Of the Complement And Coagulation Cascadesmentioning
confidence: 99%